PENGARUH LINGKUNGAN SOSIAL DALAM PSIKOLOGI ISLAM - Liatus Wiattri; Khula Khusnita; Sheila Hariry (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Psychological crises in children and adolescents are often triggered by the weak influence of a positive social environment. This article discusses the influence of the social environment on the psychological development of individuals from an Islamic psychology perspective. The social environment, which includes family, school, community, and peers, plays an important role in shaping a person's personality, self-control, and emotional balance. This study uses a qualitative approach through a literature study method, by analyzing five relevant scientific works. The results of the study indicate that the quality of interaction in the social environment greatly determines the direction of individual psychological development. In the context of Islam, the social environment is not only a space for interaction, but also a vehicle for moral and spiritual education that supports the formation of a perfect human being. This finding emphasizes the importance of creating a religious, communicative, and educational social environment as part of a strategy to build a mentally healthy and spiritually strong generation.